(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Coffee is a widely consumed beverage that may contain trace amounts of polycyclic aromatic hydrocarbons (PAHs) like Benzo[a]pyrene (BaP) due to environmental contamination or roasting processes. A method for extracting and quantifying Benzo[A]pyrene (B[a]P)was evaluated using varieties of coffee samples. The samples were extracted with acetone, followed by saponification and cyclohexane extraction. The extracts were purified by chromatography. BaP is a known carcinogen, so it is important to monitor levels in coffee as it’s a popular beverage consumed by people on regular basis. This study developed and validated an HPLC method for identifying and quantifying BaP in different coffee brands. The quantification was done by HPLC with a reverse-phase HPLC system of C18 Kromasil 100 column and UV-visible detection under isocratic conditions. The developed HPLC method is simple, sensitive, and suitable for routine monitoring of BaP in coffee samples to ensure consumer safety.